Evidence of a Systemic Predisposition to Chondrocalcinosis and Association Between Chondrocalcinosis and Osteoarthritis at Distant Joints: A Cross‐Sectional Study. Issue 7 (1st July 2013) - Abhishek, A.; Doherty, S.; Maciewicz, R.; Muir, K.; Zhang, W.; Doherty, M.
<x xml:space="preserve">Abstract</x> Objective To determine whether there is a systemic predisposition to chondrocalcinosis (CC) and to examine the association between CC and osteoarthritis (OA) at distant joints. Methods We performed a cross‐sectional study embedded in the Genetics of Osteoarthritis and Lifestyle (GOAL) database (n = 3, 170). All GOAL participants have had radiographs of the knees, hands, and pelvis performed. These were scored for OA at the knee, hip, wrist, and metacarpophalangeal (MCP) joints and for CC at the knee, hip, wrist, and symphysis pubis joints and for MCP joint calcification. Systemic predisposition to CC was established using cluster analysis. Odds ratios (95% confidence intervals) were used to examine the association between CC at the index and distant joints, CC and OA at the same joint, and index joint OA and distant joint CC. We adjusted for age, sex, and body mass index, and for distant joint OA, if required. Results Joints with CC clustered together. This was also observed when participants with OA were excluded from the analysis. CC at each joint was associated with CC at distant joints. Knee and wrist OA but not hip OA was associated with CC at the same joint. MCP joint OA was associated with MCP joint calcification. Knee OA was associated with CC at other joints, and this was independent of OA at the distant joint. There was no association between hip OA and distant joint CC. Conclusion There is a systemic predisposition to the apparently sporadic CC. OA is associated with CC at the same joint and at distant joints, except hip OA, which is not associated with hip CC or with CC at distant joints.